2001
DOI: 10.1007/s001670000166
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stability in the anterior cruciate ligament deficient knee

Abstract: Some individuals can stabilize their knees following anterior cruciate ligament rupture even during activities involving cutting and pivoting (copers), others have instability with daily activities (non-copers). Movement and muscle activation patterns of 11 copers, ten non-copers and ten uninjured subjects were studied during walking and jogging. Results indicate that distinct gait adaptations appeared primarily in the non-copers. Copers used joint ranges of motion, moments and muscle activation patterns simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
402
7
27

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 358 publications
(469 citation statements)
references
References 25 publications
33
402
7
27
Order By: Relevance
“…These results are in agreement with the fact that both muscles, Hamstrings (knee flexor) and Quadriceps (knee extensor), are stabilizing the knee when the ACL is ruptured (Chmielewski et al, 2001;Rudolph et al, 2001). These muscles control the joint to avoid high displacements of the tibia with respect to the femur.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…These results are in agreement with the fact that both muscles, Hamstrings (knee flexor) and Quadriceps (knee extensor), are stabilizing the knee when the ACL is ruptured (Chmielewski et al, 2001;Rudolph et al, 2001). These muscles control the joint to avoid high displacements of the tibia with respect to the femur.…”
supporting
confidence: 89%
“…Regarding subjects with ACL deficiency, differences have been observed at the joint level as well as at individual EMG signals (Houck et al, 2007;Knoll et al, 2004;Rudolph et al, 2001;Serrancoli et al, 2014).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Although patients were instructed at the time of MRI testing to relax their leg and not resist the applied loads; some muscle activation was likely to occur to maintain that position for the full scan time affecting stability measurement. Because quadriceps strength and ROM are considered factors that affect knee stability, the excellent ROM and quadriceps strength in our cohort may have contributed to the lack of statistical significance in the stability measures [29,37]. In addition, 11 patients had meniscal pathology, composing less than one-third of the meniscus, at the time of their ACL reconstruction.…”
Section: Discussionmentioning
confidence: 95%
“…Anatomic placement is considered optimal to provide maximum stability. Traditionally, femoral tunnel drilling has been done through a previously drilled tibial tunnel [1,11,23,26]; however, the results of this approach have sometimes been disappointing because a more vertical graft could limit rotational stability [37,45]. Some have therefore suggested that the femoral tunnel be created independently of the tibial tunnel through the use of an anteromedial drilling portal [8,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, muscle activation patterns in gait have drawn considerable attention in the knee osteoarthritis literature. It was often reported that patients co-contract longer, co-contract more, or have higher muscle activity during walking than controls (e.g., Benedetti et al, 1999;Briem et al, 2007;Childs et al, 2004;Heiden et al, 2009;Hortobágyi et al, 2005;Hubley-Kozey et al, 2006;Lewek et al, 2003;Rudolph et al, 2001;Schmitt and Rudolph, 2007;Zeni et al, 2009). …”
Section: Introductionmentioning
confidence: 99%